#TITLE_ALTERNATIVE# - QINAN TAMARA (NIM: 15109026); Pembimbing: Dr. Deni Suwardhi, ST., MT.; Dr.-Ing., Ir. Himasari Hana
Ciawi city contains many villages and dense housing located in the Ciliwung watershed, thus indirectly causing damage to the river upstream and flooding in the capital city of Jakarta . To address the problem of the improper development of Ciliwung watershed, a real-time visualization to represent the actual condition of Ciliwung watershed is needed. Today, 3D modeling continues to develop. One development is the creation of the concept of CityGML. Therefore, this study was conducted to create 3D models of the Ciliwung watershed in Cibanon and Pandansari village, Bogor, West Java for use in landscape architectural design and to display the 3D model in the CityGML format. In practice, the data is obtained from aerial photographs captured using unmanned air vehicle (UAV). The data is a result of aerial triangulation processing from two different pieces of software, Isat and Agisoft Photoscan. Both of these data will be compiled and modeled in three dimension so as to produce two three-dimensional visualization that will be saved in the CityGML format. The results of this study are two 3D model visualizations of two samples of Ciliwung in research area. The two models were compared based on the accuracy of aerial triangulation residual value and point-to-point observation. The results of the analysis states that the Isat-processed model is more accurate compared to the Agisoft Photoscan model. Both models have visually represented the object that suits the needs of landscape architecture. However, when the file is saved into the CityGML format, objects that can be represented are only in the form of buildings.